A facile method for synthesis rGO/Ag nanocomposite and its uses for enhancing photocatalytic degradation of Congo red dye - Ali, Mohamed H. H.; Goher, Mohamed E.; Al-Afify, Afify D. G.; El-Sayed, Siliem M. (SN applied sciences, 2022)
The enhancing breakdown of dyes using facile, novel and eco-friendly photocatalyst without remaining any hazards secondary intermediates from the dye species regarded one of the most challenges to the healthy world. A novel facile method was used to synthesize reduced graphene oxide (rGO) with various doping ratios of silver nanoparticles (Ag NPs) and applied as photocatalyst to enhancing removal of Congo red (CR) dye using UV light irradiation from aqueous solution. Some characterization features such as UV-diffuse reflectance spectra, TEM, SEM, FTIR, X-ray diffraction, and EDX were measured to demonstrate the energy gap, morphology, size distribution, crystalline nature, phase structure, and elemental compositions of as-synthesized nanoparticles. The effect of some important factors such as pH of solution, initial CR concertation (Co), amount of rGO@Ag (g) and contact time (t) were studied to detect the optimum adsorption condition. The results indicated that, the maximum CR dye photodegradation is obtained at pH 7, 120 min, 50 mg/L initial CR concentration and 0.4 g/L photocatalyst dosage. The photodegradation data declared that, the higher the Ag doping ratio, the higher the degrading efficiency. Isotherm and kinetic studies showed that Langmuir and Freundlich models and the pseudo-second-order model are well fitting the adsorption process with maximum CR adsorption values ranging between 86.95 and 98.04 mg/L with corresponding R 2 > 0.99. Article Highlights 1. A cheap eco-friendly and facile method to synthesis rGO@Ag NPs 2. photodegradation of Congo red dye using as-synthesized rGO@Ag NPs under UV irradiation light 3. a promising photodegradation process of CR dye from aqueous solution was achieved